A unifying principle for multispecies coexistence under resource fluctuations - James A. Richardson; Jan Engelstädter; Andrew D. Letten (Proceedings of the National Academy of Sciences, 2025)
Resource fluctuations are ubiquitous in nature and yet are generally assumed to play a limited role in the maintenance of biodiversity. We challenge this assumption by analyzing resource competition dynamics under conditions where prevailing theory does not hold. We show that multispecies coexistence can be sustained when species are able to specialize on different temporal patterns of resource variability, including the asymmetries and periodic extremes commonly observed in natural systems. We further show how this partitioning of the statistical moments of the resource distribution provides a unified framework for explaining coexistence in variable resource environments. The multiplicity of niches we find in a single fluctuating resource highlights the potential for anthropogenic changes in resource regimes to drive cascading biodiversity losses.